EFEKTIVITAS RELAKSASI OTOT PROGRESIF UNTUK MEREDUKSI STRES AKADEMIK SISWA SEBAGAI TEKNIK DALAM LAYANAN BK - Irsad Hidayat; Asmidir Ilyas (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research was 1) to identify the student’s academic stress level, 2) to identify the difference of the student’s academic stress level before and after progressive muscle relaxation training, 3) to test the efficacy of progressive muscle relaxation to reduce the student’s academic stress level. Research methods used are quantitative methods with pre-experiment design. The subjects of research are 20 students from class IX MTs Negeri 3 Padang with stress level from medium to high. Research finding: 1) the student’s academic stress level before a treatment was 146.6 (66.6%), 2) the student’s academic stress level after a treatment was 177.6 (53.5%), 3) there was a tendency that academic stress levels after progressive muscle relaxation was reduced.Keywords: academic stress, progressive muscle relaxation